Obtaining and Characterization of Hybridomas Producing Monoclonal Antibodies to Shiga-Like Toxins of I and II Types - G. V. Kuklina; S. S. Ipatov; D. V. Pechenkin; A. V. Eremkin; A. A. Kytmanov; M. Yu. Dubrovin; A. S. Gorshkov (Проблемы особо опасных инфекций, 2021)
Objective – obtaining and characterization of hybrid cell lines producing monoclonal antibodies against I and II types of shiga-like toxins.Materials and methods. Shiga-like toxins obtained in “48thCentral Research Institute” of Ministry of Defense of Russian Federation (Kirov), BALB/c mice, myeloma cells SP2/0-Ag14 were used in research. Immune splenocytes and SP2/0-Ag14 myeloma cells were fused according to G. Kohler and C. Milstein method in De St. Fazekas and D. Scheidegger modifcation using 50 % polyethylene glycol. Hybrid cell lines producing specifc monoclonal antibodies were cloned by limited dilutions. Hybridomas growth and producing properties were studied in vitro and in vivo. Specifc activity of immune sera, culture and ascitic ﬂuids were studied by indirect ELISA. Monoclonal antibodies from ascitic ﬂuids were precipitated by saturated ammonium sulfate, followed by ion exchange chromatographyResults and discussion. 8 hybridomas producing monoclonal antibodies against I and II types shiga-like toxins were obtained. Hybridomas are characterized by stable proliferation and antibody-producing activity during 10 passages in vitro and 3 passages in vivo (observation period). Obtained monoclonal antibodies can be used for ELISA detection of I and II types shiga-like toxins. Minimum detectable concentration of shiga-like toxins in sandwich ELISA is 1 ng/ml. The possibility of detecting shiga-like toxins without typical diﬀerentiation was shown when using in the enzyme immunoassay a polyreceptor mixture of monoclonal antibodies for sensitizing the plate and a polyspecifc mixture of immunoperoxidase conjugates.